Can EBUS-TBNA Provide an Accurate Diagnosis in Patients Found to Have Enlarged or FDG-avid Lymph Nodes During Surveillance of Previously Treated Lung Cancer?. Issue 2 (April 2015) - Evison, Matthew; Crosbie, Philip A.J.; Califano, Raffaele; Summers, Yvonne; Martin, Julie; Barber, Philip V.; Booton, Richard
<x xml:space="preserve">Abstract</x> Background: Reliable pathologic sampling methods are pivotal in the management of lung cancer patients who have undergone either curative intent or palliative treatment previously. Early diagnosis of localized disease recurrence may facilitate further curative treatment and rebiopsy at the point of disease progression during palliative treatment can inform further management. This study assessed the performance of endobronchial ultrasound-guided transbronchial needle aspiration (EBUS-TBNA) lymph node sampling in a cohort of such patients. Methods: A retrospective analysis of a prospectively maintained database of EBUS-TBNA procedures at the University Hospital of South Manchester from August 2010 to August 2013. All patients with previously treated lung cancer and suspected nodal metastases (defined as nodal enlargement on CT>10 mm in the short axis or abnormal FDG avidity on PET-CT) were included. Results: The sensitivity of EBUS-TBNA, on a per patient and per lymph node basis, was 91.4% and 91.8%, respectively (CI, 80.8%-96.5%). The corresponding NPV was 87.5% and 89.7%, respectively (CI, 76.4%-95.9%). There were no major complications and 3 (5.4%) minor complications. From the malignant EBUS-TBNA samples, the NSCLC-NOS rate was 3.2% and adequate tissue for molecular testing was provided in 100% of the cases (16/16). Conclusions: EBUS-TBNA is a safe and highly effective diagnostic procedure in suspected nodal metastases after previous treatment for lung cancer. The sensitivity and NPV are equivalent to EBUS-TBNA in the diagnosis of "new" lung cancer.